Notificações espontâneas de eventos adversos a medicamentos hospitalares: estudo piloto - Aguiar, Taís Orlandin Dias de [UNESP]; Capuccho, Helaine Carneiro [UNESP]; Varallo, Fabiana Rossi [UNESP]; Mastroianni, Patricia de Carvalho [UNESP] (My University, 2015)
Introduction: Post-marketing surveillance of drugs aims to detect problems related to safety, effectiveness and quality. The identification of adverse drug events (ADE) is made, mainly, by health professionals´ spontaneous reporting. This method allows risk communication in pharmacovigilance and contributes for market regulation. Objective: To estimate the prevalence of adverse drug reaction (ADR) and the suspicions of therapeutic failure (TF) reported by health professionals; to verify the active principle and type of drugs related to ADE, seriousness, causality, production mechanism and clinical manifestation of the events identified. METHODS: A cross-sectional study was performed in a teaching and public hospital which integrates the Sentinel Hospital Network, in 2008. ADR seriousness was classified according to intensity (mild, moderate, serious and lethal); drugs associated with ADE were categorized according to type (brand name drugs and non-brand name drugs); causality was imputed with Naranjo algorithm and the mechanism of occurrence was analyzed according to Rawlins e Thompson definitions (A or B). Results: There were 103 ADE reports in the period, of which 39 comprised TF and 64 ADR. Nurses reported the most ADE (53.4%). The majority of ADR were classified as type A (82.8%), mild (81.3%), possible (57.8%), according to causality assessment, and related to brand name drugs (20/35). Human immunoglobulin, docetaxel and paclitaxel were the drugs frequently associated with ADR. TF arising from no-brand name drugs (26/29), regarding, mainly, midazolam and ganciclovir. Conclusion: The results of the ADE report contribute for proposition of trigger tools for intensive monitoring of drug safety, as well as for the supplier qualification and for the improvement of quality products.

Introducción: La vigilancia poscomercialización de medicamentos tiene como objetivo la detección de problemas de seguridad, efectividad y cualidad. La identificación de acontecimientos adversos a medicamentos (AAM) se realiza, principalmente, por las notificaciones espontáneas de profesionales de la salud. Este método permite la comunicación de riesgos en farmacovigiláncia y contribuye para la reglamentación del mercado. Objetivo: Estimar la prevalencia de reacciones adversas a medicamentos (RAM) y las sospechas de inefectividad terapéutica (IT) notificadas por los profesionales de la salud; verificar los fármacos y el tipo de medicamento envueltos; la gravedad; causalidad, el mecanismo de producción y las manifestaciones clínicas de los acontecimientos. Metodología: Se ha realizado, en 2008, un Estudio transversal en un hospital de público de enseñanza , integrante de la Red de Hospitales CentinelasLa gravedad de las RAM fue clasificada según la intensidad (leve, moderada, grave y fatal); los medicamentos asociados a los AAM fueron categorizados según el tipo (similar o de marca); el grado de causalidad fue imputado con el algoritmo de Naranjo y el mecanismo de ocurrencia de las RAM fue evaluado según la definición de Rawlins y Thompson (A y B). Resultados: Durante el período del estudio hubo 103 notificaciones, de las cuales 39 eran de IT y 64 de RAM. Los enfermeros fueran los principales notificantes (53,4%). La mayoría de las RAM fueron del tipo A (82,8%), leves (81,3%) de causalidad posible (57,8%) y relacionadas con los fármacos de referencia (20/35). La inmunoglobulina humana, docetaxel y paclitaxel estaban comúnmente asociados con RAM. Las IT se asociaron al uso de medicamentos similares (26/29), especialmente midazolam y ganciclovir. Conclusiones: Los resultados de las notificaciones contribuyeron para la propuesta de rastreadores de seguimiento de seguridad de medicamentos. Además, permitió la calificación de proveedores de medicamentos en el hospital.

Introdução: A vigilância pós-comercialização de medicamentos visa à detecção de problemas de segurança, qualidade e efetividade. A identificação de eventos adversos a medicamentos (EAM) é realizada, principalmente pela notificação espontânea por profissionais da saúde. Este método permite a comunicação dos riscos em farmacovigilância e contribui para a regulamentação do mercado. Objetivo: Estimar a prevalência de reações adversas a medicamentos (RAM) e de suspeitas de inefetividade terapêutica (IT) notificadas por profissionais da saúde; verificar os fármacos e o tipo medicamentos envolvidos, a gravidade, a causalidade, o mecanismo de produção e as manifestações clínicas dos EAM notificados. Métodos: Estudo transversal foi conduzido, em 2008, num hospital de ensino de alta complexidade e integrante da Rede Sentinela. A gravidade das RAM foi classificada quanto à intensidade (leve, moderada, grave e letal), o grau de causalidade foi imputado com o algoritmo de Naranjo e o mecanismo de ocorrência da RAM foi analisado segundo a definição de Rawlins e Thompson (A e B). Os medicamentos associados aos EAM foram categorizados segundo o tipo (referência ou similar). Resultados: No período, houve 103 notificações, sendo 39 de IT e 64 de RAM. As prevalências de EAM/paciente e EAM/leito foram, respectivamente, 0,3% e 11,9%. O enfermeiro foi o principal notificador (53,4%). A maioria das RAM foi classificada como sendo do tipo A (82,8%), leve (81,3%), de causalidade possível (57,8%) e relacionada aos medicamentos referência (20/35). Imunoglobulina humana, docetaxel e paclitaxel foram os fármacos comumente associados à RAM. As IT relacionaram-se ao uso de medicamentos similares (26/29), principalmente dos fármacos midazolam e ganciclovir. CONCLUSÕES: Os resultados das notificações contribuíram para a proposição de rastreadores de monitoramento da segurança dos medicamentos e na qualificação de fornecedores para a instituição.
Spontaneous reporting of hospital adverse drug events: pilot study
Notificaciones espontáneas de acontecimientos adversos a medicamentos hospitalários: estudio piloto
Keywords: Safety management; Product surveillance; Postmarketing; Adverse drug reaction reporting systems; Pharmacovigilance; Drug utilization; Administración de la seguridad; Vigilancia de productos comercializados; Sistemas de registro de reacción adversa a medicamentos; Farmacovigilancia; Utilización de medicamentos; Gerenciamento de segurança; Vigilância de produtos comercializados; Sistemas de notificação de reações adversas a medicamentos; Farmacovigilância; Uso de medicamentos